GFF Guidance Note: Inclusive Multi-stakeholder Country Platforms in Support of Every Woman Every Child - Global Financing Facility (Global Financing Facility, 2018)
The aims of this paper are: 1) to highlight how multi-stakeholder country platforms, built on development effectiveness principles, in line with the globally agreed recommendations of IHP+2, can be reinforced within the framework of the Global Strategy and its supporting mechanisms and are key to the Global Strategy’s successful implementation; and 2) to lay out key considerations for new multi-stakeholder country platforms, along with the relevant mechanisms and a minimum set of standards to support the process of national coordination among actors engaged in RMNCAH. This guidance note is intended to serve as a resource for countries committed to implementing the Global Strategy. This includes the 62 high-burden, low- and lower-middle income countries that are eligible to receive resources from the GFF Trust Fund. It will build on lessons from countries that have already developed or are currently developing prioritized RMNCAH Strategies or Investment Cases (IC)4 aligned with their broader national health plans and planning cycles and processes, for purposes of mobilizing resources, including from the GFF Trust Fund and other sources of funding. The GFF, H6 and PMNCH seek to bring together a broad set of partners and leverage their unique roles, comparative advantages and value added to maximize impact for improved outcomes for women, children and adolescents.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; gender / género; health / saúde; youth / juventude

Youth initiatives: Supporting citizen engagement with government and civic life - Orrnert, Anna (GSDRC, University of Birmingham, 2018)
There is a large volume of literature on youth participation in development, including on the benefits of involving young people in local, national, regional and global governance initiatives. Although not as voluminous, there is also a significant body of work on youth participation in civic life, though much of this focuses on issues of education and employment (Oxfam 2016) as well as health (particularly initiatives related to HIV/ AIDS). It was not possible to identify a large body of literature around more multi-faceted and holistic initiatives (for example, involving different themes and connecting at different levels).
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; citizenship & participation / cidadania e participação; civil society / sociedade civil; youth / juventude

GFF Implementation Plan for the Gff Civil Society Engagment Strategy - Global Financing Facility (Global Financing Facility, 2017)
The implementation plan for the civil society engagement strategy (CSES) is developed to provide civil society organizations in countries (CSOs) with an operational framework to strengthen their engagement in the GFF process with a view to supporting the achievement of the objectives of the GFF and national investment cases. The plan reflects and builds on, and should be read in conjunction with the CSES. It is shaped and informed by GFF country implementation experiences to date, 12345 as well as the results of a targeted 2017 survey sent to CSOs working in GFF countries. The survey was geared towards understanding: 1) the civil society landscape in countries; 2) the level of knowledge of the GFF processes by CS; 3) priority actions CS can take to strengthen their engagement in the GFF processes and to support the achievement of the RMNCAH investment cases; and 4) what resources CS might need to better engage with national platforms and planning processes and to implement the identified supportive actions. The survey was sent to 18 organizations in 12 GFF countries and had a 61% response rate.
Keywords: #Policy Document / Documento de Política; *indexed; *tagged; G - Rest of the World / Resto do Mundo; GFF (Global Financing Facility); Health PEA; L - english / inglês; civil society / sociedade civil; development partners / parceiros de cooperação; health / saúde

Citizen voice and state accountability: towards theories of change that embrace contextual dynamics - Tembo, Fletcher (Overseas Development Institute, 2012)
The development industry is increasingly pushing practitioners to achieve results, and to do better in demonstrating what works, what does not, and explaining why. There is a growing interest in going beyond the measurement of results to being able to understand the basis for success or failure. Consequently, the development of explicit theories of change (ToCs) is starting to be viewed as central to this process, as a key part of what constitutes ‘rigour’ in impact evaluations. Citizen voice and accountability (CV&A) project interventions produce and reproduce diverse outcomes that are not amenable to linear models of ToCs. This paper uses a critical analysis of CV&A cases from the Mwananchi Governance and Transparency Fund (GTF) programme to examine how citizen voice and accountability happens in different governance contexts. The analytical framework used in this paper draws on the well-known tools of outcome mapping (OM) and political economy analysis (PEA). Key points: Enabling citizens to influence government accountability is a complex process involving political dynamics at the citizens’ interface with state institutions; Developing explicit theories of change (ToCs) from the start of programme planning helps planners delve into complex citizen–state dynamics; and Fusing political economy analysis and outcome mapping tools can help develop a deeper understanding of these dynamics to generate more effective ways to achieve outcomes.
Keywords: #Reviews & Framing / Revisões e Organização; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; M - political economy analysis (PEA) / análise de economia política (AEP); accountability / responsabilização; civil society / sociedade civil

Citizen Participation in Auditing in Latin America: The Future Agenda - Marcos Mendiburu (Accountability Research Center and Controla Tu Gobierno)
A group of civil organizations committed to strengthening state-society synergies for accountability and Mexico’s National Audit Office (ASF) jointly organized the International Seminar on Citizen Participation and External Auditing in September 2020. More than five thousand people from 21 countries registered, and there were more than eighteen thousand virtual participants throughout the three days of the event.[1] During the seminar, participants shared an assessment on the state of the subject regionally, research on the progress made at the sub-national level in a couple of countries, SAIs practices in the region, and examples from civil society on the use of SAI-generated information. Not only was the seminar useful to discuss progress and existing gaps but also to develop a series of proposals and recommendations that could be followed by OLACEFS and the SAIs themselves to expand on this issue. Seminar participants acknowledged that citizen participation has advanced faster than its implementation by most SAIs in the region, which usually encompasses limited participation exercises. Thus, there is a risk that promoting citizen participation may constitute an effort to “be compliant” but not to generate any relevant impact on auditing. Among the factors that would explain this situation were: the false dilemma between “citizen participation” and “audit”—based on the assumption that the former could affect the independence of the SAIs and/or the objectivity of the auditing; the organizational culture of the SAIs themselves; and the limitations of the citizen reporting mechanism as the dominant practice for citizen participation. The ‘minimalist approach’ to citizen participation in auditing adopted by many of the region’s SAIs entails the need to go beyond their comfort zone and seriously consider the results and the impact of citizen participation, its sup-porting evidence, and how achievements are measured. In other words, citizen participation in audits must be results-oriented. Therefore, rigorous metrics are required on SAIs’ efforts to promote citizen participation. The data related to the implementation and results of citizen participation in audits by SAIs should be publicly disclosed on their institutional websites. At the seminar, some institutionalized practices on citizen participation in auditing were shared, such as the participatory planning of the SAI from Argentina, the Council of Civil Society Associations (COSOC) of the SAI from Chile, the articulated audit of the SAI from Colombia, and the citizen report mechanism of the SAI from Mexico. However, the engagement of indigenous communities in the audit on the quality of drinking water services con-ducted by the Costa Rican SAI in 2018 showed that an enabling legal framework or specific internal regulations are not always required for SAIs to promote citizen participation. In this case, there was no internal practice to support such participation, but the willingness to experiment was essential. The innovation in SAIs must go hand in hand with citizen participation. This experience also highlighted the importance of involving the ultimate beneficiaries of the audit: the community members themselves. It was emphasized that a broader view of citizen participation in SAIs requires an analysis of the various profiles of potential civil society participants. It also requires an understanding of the mechanisms these participants use to participate, their motivations, their possible contributions to an effective participation in an audit, and an adjustment of the practices implemented when they encounter obstacles gaining access to them. This approach also calls for adopting citizen participation practices based on a collaborative approach between citizens and SAIs instead of adopting consultative-nature practices prevalent in most institutions. This implies that citizen participation practices must be jointly created, that is, created from and with the citizens, not for the citizens. Furthermore, this approach involves citizen participation throughout the audit cycle, including during the execution and/or follow-up phase of an audit, when feasible and appropriate. Likewise, it is also necessary to promote the accountability of citizen contributions or inputs from start to end, including the actions implemented by the SAIs (reporting on their capacity to respond or ‘responsiveness’) and how these actions or responses have contributed to other actions or changes by third parties. This requires SAIs to take a different perspective when reporting their achievements to transcend audit reports (and their findings or recommendations), emphasizing their contribution to the accountability ecosystem (for example, how other oversight bodies, the media, and society have used audit products), and how this contributes to improving people’s lives. This is key to prove the added value of SAIs in today’s world. In summary, the challenges of the 21st century require public institutions to collaborate with other stakeholders, focus on results, be innovative, and use knowledge to adapt to changes in the external environment.[2] These characteristics or qualities also need to be present among SAIs. Notes [1] The seminar was broadcast on YouTube. Please note that only those who wished to obtain a certificate of attendance registered, although others connected to the live broadcast without prior registration. On the other hand, the total number of virtual participants comprises the total number of people connected in each of the sessions. [2] These qualities were pointed out by Diego Arisi, the IDB’s leading state modernization specialist, on November 20 at an event held in Bogotá, Colombia.
Keywords: #Reviews & Framing / Revisões e Organização; *indexed; *tagged; G - Rest of the World / Resto do Mundo; L - english / inglês; accountability / responsabilização; citizenship & participation / cidadania e participação; civil society / sociedade civil